Bypassing the Gut–Lung Axis via Microbial Metabolites: Implications for Chronic Respiratory Diseases - Bulanda, Edyta; Wypych, Tomasz P. (Frontiers in Microbiology, 2022)
The gut microbiome engages in constant interactions with the immune system, laying down the fundamentals of what we perceive as health or disease. The gut microbiota acts locally in the intestines and distally in other organs, such as the lungs. This influence (termed “the gut-lung axis”) constitutes the basis for harnessing the microbiome to prevent or treat chronic respiratory diseases. Within this context, two approaches gained the most attention: the diet interventions (which shape the microbiome) and the probiotics (which exert beneficial effects directly on the host). Microbial products, which constitute a means of communication along the gut-lung axis, are only now emerging as a new class of potential therapeutics. Here, we provide a comprehensive overview of microbial products active in the airways, describe the immunological mechanisms they trigger, and discuss their clinical advantages and pitfalls.